Pengaruh Variasi Konsentrasi Indole Butyruc Acid (IBA) Terhadap Pertumbuhan Anggrek (Dendrobium canaliculatum) Pada Media Tumbuh Moss Putih - Fitri, Hanin Rahma; Rahayu, Tintrim; Jayanti, Gatra Ervi; Agisimanto, Dita (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
Orchids are ornamental plants that are in demand by the public because of the beauty of their flowers and are very profitable prospects. However, orchids have a long growth phase, with one of the critical phases being acclimatization. The development of the acclimatization phase is a prerequisite for obtaining a high plantlet survival rate. Good plantlet survival is obtained with a good root system using a growth regulator auxin Indole Butyric Acid with white moss growing media. This study aimed to study the effect of variations in IBA concentration on faster root growth of Dendrobium canaliculatum orchids using white moss media. Plantlet Dendrodium canaliculatum seed culture from sub culture 3 and selected first, planted in white moss media, and treated twice a week for a month using 0.25, 0.50, 0.75, and 1.0 ml/L IBA and fertilizer NPK Mamigro 21-21-21 as much as 2 g/L. IBA concentration at 0.25 ml/L was the best concentration for the induction of new roots of Dendrobium canaliculatum orchids grown on white moss and had a high survival rate of 92%.